High performance asymmetric supercapacitors with ultrahigh energy density based on hierarchical carbon nanotubes@NiO core–shell nanosheets and defect-introduced graphene sheets with hole structure. Issue 13 (23rd January 2017) - Qiu, Zenghui; He, Dawei; Wang, Yongsheng; Zhao, Xuan; Zhao, Wen; Wu, Honglu
Abstract : In this work, we report a fast and cost-effective cobalt catalyzed gasification strategy to obtain defect-introduced graphene sheets (DGNs) with hole structure. Abstract : In this work, we report a fast and cost-effective cobalt catalyzed gasification strategy to obtain defect-introduced graphene sheets (DGNs) with hole structure. Compared with the pristine graphene, the porous DGNs display much more outstanding capacitive behaviors. An electrode based on the DGNs shows an ultrahigh specific capacitance of 256 F g −1 at 1 A g −1 and 148 F g −1 even at 20 A g −1 . In addition, hierarchical carbon nanotubes@NiO (CNT@NiO) core–shell hybrids were fabricated via a facile chemical bath deposition method, followed by thermal annealing. The resulting CNT@NiO electrode shows a considerable specific capacitance of 1000 F g −1 at 1 A g −1 . For the first time, an advanced asymmetric supercapacitor (ASC) device was successfully fabricated consisting of a porous DGN-based negative electrode and a hierarchical CNT@NiO core–shell nanosheet-based positive electrode. The device exhibits a high specific capacitance of 108 F g −1 at 0.5 A g −1 and an excellent cycling stability, with 93.5% capacitance retention after 10 000 cycles at 6 A g −1 . Due to its unique microstructures, the CNT@NiO//DGNs ASC device displays a supreme energy density of 38.1 W h kg −1 at a power density of 500 W kg −1 and even retains an energy density of 16.2 W h kg −1 at 16 000 W kg −1 (voltage window of 1.6 V). These results indicate that our ASC device is extremely valuable for energy storage applications and predict future trends toward the realization of graphene-based materials used in supercapacitors.